Effects of ASL Rhyme and Rhythm on Deaf Children's Engagement Behavior and Accuracy in Recitation: Evidence from a Single Case Design - Leala Holcomb; Kimberly Wolbers (MDPI AG, 2020)
Early language acquisition is critical for lifelong success in language, literacy, and academic studies. There is much to explore about the specific techniques used to foster deaf children's language development. The use of rhyme and rhythm in American Sign Language (ASL) remains understudied. This single-subject study compared the effects of rhyming and non-rhyming ASL stories on the engagement behavior and accuracy in recitation of five deaf children between three and six years old in an ASL/English bilingual early childhood classroom. With the application of alternating treatment design with initial baseline, it is the first experimental research of its kind on ASL rhyme and rhythm. Baseline data revealed the lack of rhyme awareness in children and informed the decision to provide intervention as a condition to examine the effects of explicit handshape rhyme awareness instruction on increasing engagement behavior and accuracy in recitation. There were four phases in this study: baseline, handshape rhyme awareness intervention, alternating treatments, and preference. Visual analysis and total mean and mean difference procedures were employed to analyze results. The findings indicate that recitation skills in young deaf children can be supported through interventions utilizing ASL rhyme and rhythm supplemented with ASL phonological awareness activities. A potential case of sign language impairment was identified in a native signer, creating a new line of inquiry in using ASL rhyme, rhythm, and phonological awareness to detect atypical language patterns.